Changing thyroid status related to pregnancy. Issue 911 (1st September 2001) - Shankar, P; Kilvert, A; Fox, C
Abstract : A case of post-thyroidectomy hypothyroidism is reported. The patient became euthyroid in three consecutive pregnancies, reverting to hypothyroid within three months of delivery on each occasion. The alteration in thyroid status is attributed to pregnancy related changes in antibody titres, though the laboratory data to confirm this are not available.